Students’ Discipline Management in Strengthening Modern Human Resources - Ilyasin, Mukhamad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This research is aimed to describe how students’ discipline management is applied in order to weakening human resources in 21st century. This research was conducted at three different Islamic schools called madrasah i.e. Madrasah Aliyah Negeri (MAN) Makassar, MAN Batu, Malang, and MAN Insan Cendekia Paser, East Kalimantan. In this case, madrasah principal, vice principal, classroom teachers, dormitory teachers, and students became participants in this research. In this case, the researcher observed and interviewed the subject in order to describe deeply regarding with the application of students’ discipline management. The result shows that there are four discipline methods applied at MAN Makassar, MAN Batu, MAN Insan Cendekia Paser i.e. the art of distribution, the control of activity, the organization of geneses, and the composition of forces. Other than that, medium to create discipline atmosphere is also appeared from hierarchical observation, normalizing judgement, and examination. Future implication regarding with students’ discipline management is also discussed in this research.